Prevalence and Associated Factors of Anaemia in Pregnancy among Women Receiving Antenatal Care at Kabale Regional Referral Hospital - Ojom, James (Kabale University, 2025)
Background: Anaemia is widespread all over the world and is of public health significance. In pregnancy, it causes maternal and fetal complications. The primary objective of this study was to determine the prevalence and associated factors of anaemia in pregnancy among women receiving antenatal care at Kabale Regional Referral Hospital. Methods: A cross-sectional study was conducted among 400 pregnant women receiving antenatal care at Kabale Regional Referral Hospital over 4 months. Pregnant women aged 15-49 years, of any gestational age were included through consecutive sampling. Demographic, socioeconomic, obstetric and nutritional data was collected using a semi-structured questionnaire. The prevalence of anaemia in pregnancy was the proportion of participants with anaemia. The Logistic regression was used to evaluate associations between anaemia in pregnancy and the independent variables. Results: A total of 400 pregnant mothers were enrolled with a mean age of 26.9 (±5.8) years. The prevalence of anaemia in pregnancy was 7.5 %( 95% CI: 5.3-10.5). At multivariate logistic regression, being aged 25-35 years ((aOR 5.67, 95% CI: (1.68 – 19.12) P-value: 0.005); having malaria in pregnancy ((aOR 4.35, 95% CI: (1.01 – 18.78) P-value: 0.049);, being undernourished((aOR 5.30, 95% CI: (1.03 – 27.18) P-value: 0.046); and having inadequate dietary diversity ((aOR 2.64, 95% CI: (1.08 – 6.47) P-value: 0.034) were independently associated with anaemia in pregnancy. Conclusions and Recommendations: This study revealed that about 1 in every 10 pregnant women receiving antenatal care at KRRH has anaemia. Anaemia in pregnancy likelihood is higher among those; aged 25-35 years, have malaria in pregnancy, are undernourished and have inadequate dietary diversity. It is recommended to emphasize efforts to prevent malaria among pregnant women, do nutrition education and community engagements on healthy nutrition for pregnant women, screen for anaemia among pregnant women aged 25-35 years and further studies to determine the type of anaemia among pregnant women.